Governance Indicators for Development - Oman, Charles P.. (OECD Development Centre Policy Insights, 2006)
The use of governance "indicators" is booming. These indicators are supposed to quantify the quality of a country's governance institutions by considering, for example, the extent of corruption in the economy, the quality of public and private regulatory systems, the prevalence of "rule of law", the level of political stability, and the effectiveness of government